Estimasi Daya Dukung Perairan Pesisir Kabupaten Pamekasan dalam Menerima Limbah Budidaya Udang Vannamei - Moh Ismail; Indah Wahyuni Abida; Endang Tri Wahyurini (UM Purwokerto Press, 2022)
Vannamei shrimp cultivation business is an aquaculture business that has increased every year, both from the amount of production and the cultivation technology used. Vannamei shrimp cultivation in Madura is one type of work that develops by utilizing unproductive land and salt ponds being converted into vannamei shrimp ponds. Pamekasan Regency is one of the regencies that carry out the development of vannamei shrimp farming business with an intensive system. The development of vannamei shrimp cultivation is not in line with the conditions of the aquatic environment, this is because aquaculture activities produce waste in which aquaculture waste is directly discharged into the waters. The research was carried out on February 1, 2022 to April 1, 2022 in Candi Village, Galis District, Pamekasan Regency. Based on the results of the study, it was found that the load of organic waste in the form of TSS that was discharged into the waters during one maintenance cycle was 137.25 kg and 143.38 kg/0.3 ha when pouring the entire volume of pond water (3000 m3) into the waters. Based on the carrying capacity of coastal waters, the maximum amount of waste in the form of TSS that can be accommodated by the coastal waters of Pamekasan Regency is 441.39 tons/day. The amount of waste generated from intensive system vannmei shrimp farming activities in Pamekasan Regency is 55,983.26 tons for one year and 153.38 tons/day. The results showed that the waste produced was still below the maximum waste that could be accommodated by the waters of Pamekasaan Regency.